Priprave na konec vojne in osvoboditev Slovenije - Repe, Božo (Studia Historica Slovenica, 2016)
The Second World War was the biggest turning point in the history of Slovenes in the 20th century. Slovenes resisted the destruction, and the Slovene Partisan Army, from March 1945 included in the Yugoslav Army, greeted the war with some 37,000 fighters (some 80,000 people fought in partisan ranks in total). The Slovene Partisan Army, under the leadership of the Liberation Front, was part of a much wider national liberation movement with a branched organization. During the war, the Liberation Front also created new authorities. Members of the Liberation Front fought for four years, one month and eight days. The Slovene Partisan Army was an integral part of the NLAPD and the Anti-Fascist Coalition, but it fought alone, except in the concluding operations. It had its own command staff, never left Slovenia, and operated on the entire Slovene ethnic territory, which it also liberated or took part in the liberation thereof.
Keywords: druga svetovna vojna; NOB; partizani; Slovenija; slovenska vojska; svetovna vojna 1939-1945